Effect of Exogenous Interferon on Rubella Virus Production in Carrier Cultures of Cells Defective in Interferon Production - Mifune, Kumato (1970)
An established cell line (Vero) defective in interferon production was used to evaluate the role of interferon in chronic rubella virus infections of cell cultures. Inoculation of Vero cells with a low multiplicity of virus resulted in the development of carrier cultures which had the characteristics of a regulated infection. Although added interferon did not alter rubella virus production in carrier cultures of cells capable of producing interferon, such added interferon caused a dramatic reduction of virus production in the carrier cultures of Vero cells. There was a reduction of the fraction of cells producing virus in Vero carrier cultures, but not in carrier cultures of other cells upon incubation in the continual presence of rubella virus antibodies. In addition, the fraction of infected cells fluctuated in carrier cultures in Vero cells. The data indicate that interferon is not necessary for maintaining a chronic rubella virus infection in vitro and suggest an instability of the virus genome in Vero cells.